2016
DOI: 10.1038/ncomms13982
|View full text |Cite
|
Sign up to set email alerts
|

Proximity does not contribute to activity enhancement in the glucose oxidase–horseradish peroxidase cascade

Abstract: A proximity effect has been invoked to explain the enhanced activity of enzyme cascades on DNA scaffolds. Using the cascade reaction carried out by glucose oxidase and horseradish peroxidase as a model system, here we study the kinetics of the cascade reaction when the enzymes are free in solution, when they are conjugated to each other and when a competing enzyme is present. No proximity effect is found, which is in agreement with models predicting that the rapidly diffusing hydrogen peroxide intermediate is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
325
1
11

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 304 publications
(357 citation statements)
references
References 43 publications
(66 reference statements)
20
325
1
11
Order By: Relevance
“…The enhancement of the enzymatic activity observed for strep–HRP upon its loading into the IPDG can be either attributed to a protection by the gel microenvironment against protein degradation or explained by an enhancement of the catalytic activity of the bound enzymes due to confinement and/or proximity of DNA. These two effects are already known for enzymes conjugated to DNA in other configurations, but have never been described for enzymes loaded in DNA microgels. All these results show that IPDGs can acquire enzymatic activity upon crosslinking biotinylated DNA with streptavidin–enzyme conjugates.…”
Section: Resultsmentioning
confidence: 99%
“…The enhancement of the enzymatic activity observed for strep–HRP upon its loading into the IPDG can be either attributed to a protection by the gel microenvironment against protein degradation or explained by an enhancement of the catalytic activity of the bound enzymes due to confinement and/or proximity of DNA. These two effects are already known for enzymes conjugated to DNA in other configurations, but have never been described for enzymes loaded in DNA microgels. All these results show that IPDGs can acquire enzymatic activity upon crosslinking biotinylated DNA with streptavidin–enzyme conjugates.…”
Section: Resultsmentioning
confidence: 99%
“…Idan and Hess proved that the increase in direct substrate transfer due to the proximity provides an initial but temporary boost to the throughput of the cascade and loses its impact as intermediates accumulate in the surrounding container. Zhang et al . confirmed that an enhanced activity of GOx/HRP on DNA scaffold is contributed by a favorable local pH by DNA nanostructures.…”
Section: Methodsmentioning
confidence: 92%
“…The results indicate that a highly charged polyelectrolyte can attract protons to their vicinity and form a partial acidic microenvironment. We calculated the pH profile near the surface of CPO‐PMAA using the Poisson‐Boltzmann model, and found that the local pH depends on the bulk pH and the surface potential. The higher bulk pH, the larger pH difference between the local and bulk solution (see Figure d and Supporting Information for details).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the enzyme kinetic analysis of catalytic cascades in the hexagonal nanospace follows the Michaelis–Menten model (Figure d, S13). Notably, Hess and co‐workers recently clarified that the proximity played less role in this multienzyme systems while the pH value near the surface of the negatively charged DNA nanostructure contributed the better reacting environment for the immobilized enzymes . However, Niemeyer raised the several remaining questions such as the reaction‐diffusion models in the recent review .…”
Section: Figurementioning
confidence: 99%